Characterization and Stability Analysis of Biopolymeric Matrices Designed for Phage-Controlled Release - Dini, Cecilia (2014)
Alginate and low methoxylated pectin gel matrices emulsified with oleic acid were studied for phage oral delivery. Matrix structural analysis revealed that emulsified pectin (EP) gel microbeads were harder and more cohesive than those of emulsified alginate (EA). EP showed high swelling capacity and slower matrix degradation in aqueous media, suggesting that oleic acid is mainly located on the surface of EP microbeads. EA and EP matrices having p-nitrophenyl palmitate (C-16 ester) as tracer dissolved into oleic acid and in the presence of lipase confirmed this hypothesis which is consistent with EP better phage protective capability. Surface analysis of gel microbeads by scanning electron microscopy revealed strong differences between EP and EA gel microbeads. Phage release kinetics was tested using semi-empirical mathematical models. Experimental curve best fitted the Korsmeyer–Peppas model, predicting transport mechanisms according to the high swelling and degradation of EP. The proposed encapsulation model represents an innovative technology for phage therapy, which can be extrapolated to other therapeutic purposes, using a simple environmentally friendly synthesis procedure and cheap food-grade raw materials.